2020
DOI: 10.1016/j.cageo.2020.104456
|View full text |Cite
|
Sign up to set email alerts
|

1D geological imaging of the subsurface from geophysical data with Bayesian Evidential Learning

Abstract: Imaging the subsurface of the Earth is of prime concern in geosciences. In this scope, geophysics offers a wide range of methods that are able to produce models of the subsurface, classically through inversion processes. Deterministic inversions lack the ability to produce satisfactory quantifications of uncertainty, whereas stochastic inversions are often computationally demanding. In this paper, a new method to interpret geophysical data is proposed in order to produce 1D imaging of the subsurface along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…However, the threshold might be approximated using synthetic benchmarking, as presented here. A similar observation has been made for other approximate Bayesian methods (e.g., [13]).…”
Section: Multi-layer Inversionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the threshold might be approximated using synthetic benchmarking, as presented here. A similar observation has been made for other approximate Bayesian methods (e.g., [13]).…”
Section: Multi-layer Inversionsupporting
confidence: 80%
“…Highly-parametrized models result in computationally expensive forward model runs that limit the applicability of MCMC methods [11]. Only recently, efficient approximations of the posterior distribution have been proposed for geophysical problems, while using innovative methods, such as the Kalman ensemble generator (KEG, [12]) or Bayesian Evidential Learning [13]. Those techniques rely on a smaller number of forward model runs and are, thus, less expensive.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, heterodox transients can be generated for a dipole potential measurement by subtracting two pole measurements (two P1 potentials). In the examples shown so far, only 2D anomalies that produce heterodox transients have been presented, but anomalies in a 1D model space can generate any kind of heterodox types as well (Michel et al, 2020). Furthermore, similar reasoning with comparable results applies to frequency-domain responses, where the phase of the apparent complex resistivity can change the sign or present heterodox shapes, or both.…”
Section: The Basic Mechanism For Heterodox (And Orthodox) Transientsmentioning
confidence: 76%
“…Such direct forecasting is possible because predictions often have a much-lower dimensionality than models. Nevertheless, when the data-prediction relationship is complex and highly nonlinear, BEL might overestimate uncertainty (Michel et al, 2020a), for instance when the prior uncertainty is large (Hermans et al, 2019). In such a case, classical inversion might still be needed (Scheidt et al, 2018).…”
Section: Numerical Methods Development For 4d Data Integration and In...mentioning
confidence: 99%
“…In such a case, classical inversion might still be needed (Scheidt et al, 2018). Recent advances have shown that BEL can also estimate the model parameter distributions and be used as a more traditional inversion technique (Yin et al, 2020;Michel et al, 2020a). However, such more advanced applications require further development of appropriate tools to identify highly non-linear relationships (Park and Caers, 2020) which will inevitably come at a larger computational cost (Michel et al, 2020b).…”
Section: Numerical Methods Development For 4d Data Integration and In...mentioning
confidence: 99%